A case study on the advertising techniques of Philippine Airlines in the international market after the February revolution - Arcenas, Fernando Antonio V.
This is a study of the kind of advertising techniques for the international market employed by Philippine Airlines advertisements before and after the Philippine Revolution of 1986.